Global psychological assessment with the evaluation of life and sleep quality and sexual and cognitive function in a large number of patients with acromegaly: a cross-sectional study. Issue 6 (13th December 2022) - Pivonello, Rosario; Auriemma, Renata Simona; Delli Veneri, Alessandra; Dassie, Francesca; Lorusso, Riccardina; Ragonese, Marta; Liotta, Marco; Sala, Elisa; Zarino, Barbara; Lai, Elisa; Urbani, Claudio; Bogazzi, Fausto; et al.
Abstract: Objective: Acromegaly is associated with somatic disfigurements which impair self-perception of well-being and quality of life. Nowadays, limited data are available on the interplay between hormonal excess and psychological discomfort. The study aimed at investigating the psychological profile, sleep quality, sexual function, cognitive functions, and quality of life in patients with acromegaly. Methods: In 223 acromegaly patients from 5 referral centres, global psychological profile, sleep quality, sexual function, cognitive function, and quality of life were investigated. Results: Depression was found in 30% of patients, and anxiety in two-thirds, together with severe discomfort in body image mainly in women. Obstructive sleep apnoea syndrome risk and sleep disorders were found in >50% of patients and daily sleepiness in 20%. Sexual dysfunction was reported in most of the patients, with the most severe impairment in women. Cognitive functions were compromised in 10% of cases. Disease duration and patient's age and gender were the main determinants of these psychopathological conditions. Depression ( P = 0.047), somatic-affective mood lowering ( P = 0.021), state ( P < 0.001) and trait ( P = 0.013) anxiety, and body image distortion in body uneasiness test A ( P < 0.001) and B ( P = 0.006) were significantly worsened in patients <45 years and slightly worsened in those with disease duration less than 2 years. Male ( P < 0.001) and female ( P < 0.001) sexual function scores were significantly worsened in patients aged >64 years and slightly worsened in those with disease duration for more than 10 years, particularly in presence of cardiometabolic and respiratory complications. Cognitive symptoms were slightly worsened in older patients and in those with long disease duration. Conclusions: Acromegaly is associated with a relevant impairment of psychological profile persisting despite remission and long-term medical treatment.